The impact of the COVID-19 pandemic era on children with primary headache: a questionnaire survey study and literature review - Yoon, So Yeon; Kim, Hye Min; Yi, Yoon Young (Frontiers in Pediatrics, 2023)
The coronavirus disease (COVID-19) pandemic has resulted in individual isolation and secondary problems, especially in children. Research on the effect of the social isolation on children with primary headache is limited. This study aimed at exploring the effects of environmental changes caused by COVID-19 on headache in children.This cross-sectional survey study enrolled school-aged children (age, 8-16 years) with headache who were able to complete the questionnaire from a Pediatric Headache Clinic between January 2021 and December 2022. Headache diaries for all patients were in their medical records and two questionnaire responses were requested at a 3-month interval. The questionnaires included headache type, frequency, previous medical conditions, family history, Pediatric Migraine Disability Assessment scores (PedMIDAS) scores, changes in daily life after COVID-19, and factors that aggravated headaches associated with social distancing.We identified 35 patients who were diagnosed with primary headache and continued to visit our outpatient clinic for at least 3 months. Among them, 33 (15 males and 18 females) patients responded to the first survey. The average age (± SD) of patients was 12.5 ± 1.9 years. PedMIDAS scores were not affected by the COVID-19 infection history. Prolonged use of masks and increased use of digital devices were reported as the most common factors that aggravated headache during the pandemic era.COVID-19 did not affect in worsening primary headache in children. However, the pandemic can introduce various changes in daily life, which in turn can affect the management of headache. By gathering feedback regarding the thoughts of the patients on the impact of the current pandemic environment, patient counseling on the precautions and management can be conducted in advance in the case of repeated lockdown in the future.